Exercise is a potent stimulus for enhancing circulating DNase activity - Velders, M.; Treff, G.; Machus, K.; Bosnyak, E.; Steinacker, J. M.; Schumann, U. (Clinical Biochemistry, 2014)
To elucidate cell free DNA (cfDNA) clearance kinetics following an acute bout of high intensity exercise by measuring circulating DNase activity reduction (AR). Serum cfDNA concentration and DNase-AR were measured prior to and post (immediately post, 7 and 30 minutes post) an acute bout of rowing exercise until exhaustion. Serum cfDNA concentration was significantly (P=.001) elevated immediately post (2.5-fold) and 7min post exercise (2.3-fold) with a return close to baseline at 30 minutes post exercise (1.5-fold). The rise in cfDNA was accompanied by a concomitant, significant (P=.001) decrease in serum DNase-AR from 15.1% prior to exercise to 3.1% AR at cessation of the exercise test and 7min post exercise (3.9% AR). DNase-AR returned close to baseline at 30min post exercise (5.2% AR). A single bout of high intensity exercise is a potent stimulus for enhancing circulating DNase activity in healthy people. Acute exercise may therefore be considered as a non-pharmacological stimulus to trigger DNase activity. This finding may be relevant for pathological conditions associated with increased cfDNA concentrations like cystic fibrosis, where pharmacological recombinant human DNase (rhDNase) treatment has been successfully used to improve patients' health and physical function. Exercise is a potent stimulus for enhancing circulating DNase activity.